Active Flow Control Based Bleed in an Axial Compressor Cascade Using Large Eddy Simulation - Gong, Yun; Chen, Shaowen; Zeng, Cong; Wang, Songtao (Frontiers in Energy Research, 2022)
The performance of the compressor is of great importance in developing advanced engine technology, and it dramatically influences the cycle efficiency and safety of the engine. The compressor bleed requires a part of the main flow extraction from the passage, and the removal of the air flow plays an essential role in the performance of the compressor. The influence of the constant suction and pulsed suction on the flow structures and the aerodynamic performance in a compressor cascade, and the control mechanisms are numerically studied using Large Eddy Simulation. At a suction mass flow rate of 0.25% of the main flow rate, constant suction leads to a 9.36% reduction of Cpt while pulsed suction gains 24% more benefit in Cpt reduction on the basis of the constant suction with an excitation frequency of 100Hz. It indicates that the pulsed suction has more significant potential to control the loss generation in the compressor. Afterward, the flow field of the baseline, constant suction, and pulsed suction are compared to find out the flow control mechanisms of the constant suction and pulsed suction. Two different formation mechanisms of the passage vortex are found due to the excitation effect of the pulsed suction. Besides, the results of Proper Orthogonal Decomposition and Dynamic Mode Decomposition show that the pulsed suction can simplify and stabilize the compressor flow field, which could lead to a further benefit in Cpt.